New product development paradigm from the perspective of consumer innovation: A case study of Huawei's integrated product development - Chengbin Wang; Minju Chen; Qingyang Wang; Yongyan Fang; Lingguang Qiu (Journal of Innovation & Knowledge (JIK), 2024)
New product development (NPD) has become a key factor for improving enterprise competitiveness. Integrated product development (IPD) is considered a best practice for addressing the complexities of NPD, but most enterprise NPD processes face problems, such as low efficiency, long turnover, and high cost, that mismatch the demand. Using grounded theory, this article provides a case study of how Huawei's integrated product development (IPD) facilitates new product development. The research shows that Huawei has built a sustainable and replicable iterative closed loop between innovation management and business value through IPD. However, by combining consumer innovation and lean entrepreneurship theory to further analyze Huawei's IPD, it is found that there are limitations in customer development, agile development and business insight. The paper proposes an expanded approach towards new product development: incorporating lead users into the IPD process to enhance the company's business insights into NPD and integrating lean entrepreneurship theory into IPD to expedite the iteration of the company's business model. This study incorporates studies in the fields of NPD, IPD, user innovation, and lean startup theory, thus expanding the research horizon of NPD.
Keywords: O32; D22; L19; 650; Consumer Innovation; Huawei; Integrated product development; Lean Startup Theory; New product development